Comparison of Liquid-based and Conventional Cytology Smears in Fine Needle Aspirates for Diagnosis of Breast Mass - Ali Atashabparvar; Seyyede Hakimeh Sajjadi (Mashhad University of Medical Sciences, 2024)
Introduction: Breast cancer is a common malignancy in women and is the second leading cause of cancer-related deaths in the female population after lung cancer, hence its early detection and intervention has a significant effect on changing the clinical course and prognosis of the disease. The present study was performed with aim to compare the cytology results in needle sampling method between two traditional smear techniques and liquid-based cytology to detect palpable breast masses in women. Methods: The cross-sectional and descriptive study was conducted in 2019-2020 on 65 patients with a palpable breast mass referred to the surgical clinic of Shahid Mohammadi Teaching Hospital. Fine needle aspiration was performed for the patients. One portion of the aspirated material was processed in a non-gynecological ThinPrep liquid setting, while the other was prepared conventionally. The smears were compared in terms of cellularity, epithelial structure, nuclear and cytoplasmic details, and background elements using European Commission breast screening pathology criteria. Both smear methods were also compared with histopathology for confirmation. Data analysis was done using SPSS statistical software (version 23). P<0.05 was considered statistically significant. Results: The liquid-based cytology method exhibited a cellularity rate of 40% contrasting with 57% in the conventional smear, which had a significant difference (p=0.04). The liquid-based method yielded a clear background, while the conventional method displayed protein content. Cell structure comparison showed no significant difference (p=0.08). Notably, liquid-based cytology excelled in nuclear details, with 55.4% graded as excellent, compared to 49.2% in the conventional smear. High-grade cytoplasmic details were observed in liquid-based cytology, while the conventional smear rated as good. Conclusion: The liquid-based cytology method has evolved as a new method in the field of cytology and has played an effective role in reducing the limitations of conventional smear.